Nonaqueous electrolyte secondary battery

By presenting element M1 between primary particles of lithium transition metal composite oxide and adding elements M2 and Co to form a protective coating, the lithium transition metal composite oxide with high Ni content is easily associated with electrolyte in a high charging rate state. The problem of side reactions significantly improves the cycling characteristics of the battery.

CN119404334APending Publication Date: 2025-02-07PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380049063.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-09
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In a state with a high charging rate, lithium transition metal composite oxide with a high Ni content is prone to side reactions with the electrolyte, resulting in an increase in the internal resistance of the battery and a decrease in the charge and discharge cycle characteristics.

Method used

By presenting a predetermined amount of element M1 between the primary particles of the lithium transition metal composite oxide, and adding a predetermined amount of element M2 and Co to the composite oxide, a stable protective coating is formed to inhibit side reactions of the electrolyte.

Benefits of technology

It effectively suppresses side reactions of electrolytes and improves the circulation characteristics of the battery, especially in the high charging rate state, extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119404334A_ABST
    Figure CN119404334A_ABST
Patent Text Reader

Abstract

In a nonaqueous electrolyte secondary battery as an example of an embodiment, a positive electrode contains a lithium transition metal composite oxide containing Ni, Co, M1 (M1 is at least one element selected from Ca and Sr), and M2 (M2 is at least one element selected from Nb, Zr, Ti, W, Al, Mo, Fe, B, P, Mg, and Si). The lithium transition metal composite oxide is a secondary particle formed by aggregating primary particles, and the average porosity of the secondary particle is 1-5%. The negative electrode has an M2-containing coating film formed on the surface of the negative electrode mixture layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a nonaqueous electrolyte secondary battery, and more particularly to a nonaqueous electrolyte secondary battery including a lithium transition metal composite oxide having a high Ni content as a positive electrode active material. Background Art

[0002] In recent years, lithium transition metal composite oxides with high Ni content have attracted attention as positive electrode active materials with high energy density. For example, Patent Document 1 discloses a positive electrode active material having a general formula Li x Ni 1-y-z-v-w Co y Al z M 1 v M 2 w The lithium transition metal composite oxide shown in O2 is formed, where the element M 1 is at least one selected from the group consisting of Mn, Ti, Y, Nb, Mo, and W, wherein the element M 2 At least Mg and Ca. Patent Document 2 discloses a composite oxide, which is a lithium transition metal composite oxide containing Ni, Mn, and Co, and contains at least one selected from Mo, W, Nb, Ta, and Re.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2006-310181

[0006] Patent Document 2: Japanese Patent Application Publication No. 2009-289726 Summary of the invention

[0007] When the lithium transition metal composite oxide with a high Ni content disclosed in Patent Documents 1 and 2 is used as the positive electrode active material, a large amount of highly reactive Ni is present on the surface of the composite oxide particles at a high charge rate (SOC). 4 + , it becomes easy to produce side reactions between active materials and electrolytes. In addition, the decomposition products of the electrolyte produced by the side reactions are deposited not only on the positive electrode surface, but also on the negative electrode surface. As a result, the internal resistance of the battery increases and even the charge and discharge cycle characteristics are reduced.

[0008] A nonaqueous electrolyte secondary battery as one embodiment of the present invention is a nonaqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a nonaqueous electrolyte, wherein the positive electrode comprises a lithium transition metal composite oxide comprising Ni, Co, M1 (M1 is at least one element selected from Ca and Sr), and M2 (M2 is at least one element selected from Nb, Zr, Ti, W, Al, Mo, Fe, B, P, Mg and Si), wherein the content of Ni in the lithium transition metal composite oxide is 80 mol% or more relative to the total molar number of metal elements other than Li, the content of Co is 7 mol% or less relative to the total molar number of metal elements other than Li, and M1 is at least one element selected from the group consisting of Nb, Zr, Ti, W, Al, Mo, Fe, B, P, Mg and Si. The content of M2 is less than 1 mol% relative to the total molar number of metal elements other than Li, the content of M2 is less than 3 mol% relative to the total molar number of metal elements other than Li, the lithium transition metal composite oxide is a secondary particle formed by aggregation of multiple primary particles, the average porosity of the secondary particles is 1-5%, M1 exists at least at the interface between the primary particles inside the secondary particles, the negative electrode has a negative electrode composite material layer containing a negative electrode active material, and a coating containing M2 formed on the surface of the negative electrode composite material layer, and the content of M2 in the negative electrode is 1000-10000ppm relative to the total mass of the negative electrode composite material layer and the coating.

[0009] According to one embodiment of the present disclosure, a nonaqueous electrolyte secondary battery including a lithium transition metal composite oxide having a high Ni content as a positive electrode active material can suppress a decrease in capacity accompanying charge and discharge. The nonaqueous electrolyte secondary battery as one embodiment of the present disclosure has excellent cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of the embodiment. DETAILED DESCRIPTION

[0011] As mentioned above, lithium transition metal composite oxides with a high Ni content are prone to side reactions with electrolytes, especially in a state of high SOC. Therefore, when the composite oxide is used as a positive electrode active material, the decomposition products of the electrolyte are deposited on the positive electrode surface and the negative electrode surface, and the internal resistance of the battery increases, so it is believed that the cycle characteristics are reduced. The research results of the present inventors and others show that: by having a specified amount of element M1 at the interface between the primary particles constituting the Ni-containing composite oxide, and adding a specified amount of element M2 and Co to the composite oxide, the cycle characteristics are specifically improved. In this case, it is believed that a stable protective coating is formed on the positive and negative electrodes, which can effectively suppress the side reactions of the electrolyte.

[0012] The above effect becomes significant when the average porosity of the secondary particles of the composite oxide is 1 to 5%. When the average porosity of the secondary particles is 1 to 5%, it becomes easy to make the element M1 selectively exist at the interface between the primary particles, and as a result, it is believed that the effect of suppressing side reactions is increased. In other words, when the average porosity of the secondary particles is not within this range, the improvement effect of the cycle characteristics cannot be obtained, or the improvement effect becomes small.

[0013] Hereinafter, an example of an embodiment of the nonaqueous electrolyte secondary battery of the present disclosure will be described in detail with reference to the drawings. It should be noted that a combination of the various configuration features of the embodiments and modifications described below is included in the scope of the present disclosure.

[0014] Hereinafter, as a non-aqueous electrolyte secondary battery, a cylindrical battery in which a wound electrode body 14 is housed in an outer can 16 having a bottomed cylindrical shape is exemplified, but the outer shell of the battery is not limited to a cylindrical outer can. The non-aqueous electrolyte secondary battery disclosed herein may be, for example, a square battery having a square outer can, a coin-shaped battery having a coin-shaped outer can, or a bag-shaped battery having an outer shell composed of a laminate sheet including a metal layer and a resin layer. In addition, the electrode body is not limited to a wound type, and may also be a stacked electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked with a separator.

[0015] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown, the nonaqueous electrolyte secondary battery 10 includes a wound electrode body 14, a nonaqueous electrolyte (not shown), and an outer can 16 for storing the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a winding structure in which the positive electrode 11 and the negative electrode 12 are spirally wound with the separator 13 interposed therebetween. The outer can 16 is a metal container in a bottomed cylindrical shape with one end side open in the axial direction, and the opening of the outer can 16 is blocked by a sealing body 17. In the following, for the convenience of explanation, the sealing body 17 side of the battery is regarded as the upper side, and the bottom side of the outer can 16 is regarded as the lower side.

[0016] The non-aqueous electrolyte comprises a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent uses, for example, esters, ethers, nitriles, amides, and mixed solvents of more than two of these. As an example of a non-aqueous solvent, ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and mixed solvents thereof can be cited. The non-aqueous solvent can also contain a halogen substitution body (for example, fluoroethylene carbonate, etc.) in which at least a portion of the hydrogen of these solvents is replaced by a halogen atom such as fluorine. The electrolyte salt uses, for example, a lithium salt such as LiPF6. In addition, vinylene carbonate (VC) less than 5% by mass relative to the mass of the non-aqueous electrolyte can also be added.

[0017] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are alternately stacked along the radial direction of the electrode body 14 by spiral winding. The negative electrode 12 is formed to be one circle larger than the positive electrode 11 to prevent the precipitation of lithium. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the length direction and the width direction. The separator 13 is formed to be at least one circle larger than the positive electrode 11, for example, two sheets are arranged in a manner of clamping the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.

[0018] Insulating plates 18 and 19 are disposed above and below the electrode body 14 , respectively. Figure 1 In the example shown, the positive electrode lead 20 extends toward the sealing body 17 through the through hole of the insulating plate 18, and the negative electrode lead 21 extends toward the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the lid 27 electrically connected to the internal terminal plate 23, serves as the positive terminal. The negative electrode lead 21 is connected to the inner surface of the bottom of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.

[0019] A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed in the outer can 16, in which a part of the side portion protrudes inward and supports the sealing body 17. The groove portion 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 by the groove portion 22 and the open end of the outer can 16 that is pressed and connected to the sealing body 17.

[0020] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.

[0021] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 , and in particular, the positive electrode active material constituting the positive electrode 11 will be described in detail.

[0022] [positive electrode]

[0023] The positive electrode 11 has a positive electrode core and a positive electrode composite material layer disposed on the surface of the positive electrode core. The positive electrode core can use a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a thin film of the metal disposed on the surface, etc. The positive electrode composite material layer preferably includes a positive electrode active material, a binding material, and a conductive material, and is disposed on both sides of the positive electrode core except for the portion to which the positive electrode lead 20 is connected. The positive electrode 11 is made, for example, by applying a positive electrode composite material slurry containing a positive electrode active material, a binding material, and a conductive material to the surface of the positive electrode core, drying the coating, and then compressing it to form a positive electrode composite material layer on both sides of the positive electrode core, thereby being able to be made.

[0024] As the conductive agent included in the positive electrode composite material layer, carbon black such as acetylene black, ketjen black, graphite, carbon nanotube (CNT), carbon nanofiber, graphene and other carbon materials can be exemplified. As the binder included in the positive electrode composite material layer, fluorine-containing resins such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. In addition, these resins can be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide (PEO), etc.

[0025] The positive electrode 11 includes a lithium transition metal composite oxide containing Ni, Co, M1 (M1 is at least one element selected from Ca and Sr), M2 (M2 is at least one element selected from Nb, Zr, Ti, W, Al, Mo, Fe, B, P, Mg and Si), and an arbitrary component of Mn. Hereinafter, for the sake of convenience, the lithium transition metal composite oxide will be referred to as "composite oxide (Z)". The composite oxide (Z) functions as a positive electrode active material. The positive electrode active material may contain the composite oxide (Z) as the main component, or may be substantially composed of the composite oxide (Z). It should be noted that, within the scope of not impairing the purpose of the present disclosure, the positive electrode active material may also contain composite oxides or other compounds other than the composite oxide (Z).

[0026] The composite oxide (Z) is composed of the general formula Li a Ni b Co c Mn d M1 e M2 f O g (wherein, 0.8≤a≤1.2, 0.80≤b<1, 0≤c≤0.07, 0≤d≤0.10, 0<e≤0.01, 0<f≤0.03, 1≤g≤2, b+c+d+e+f=1) is a composite oxide. The composite oxide (Z) preferably has a layered structure. The composite oxide (Z) has, for example, a layered structure belonging to the space group R-3m or a layered structure belonging to the space group C2 / m.

[0027] In the composite oxide (Z), the ratio of the transition metal element present in the Li layer is preferably 3 to 7 mol% relative to the total molar number of metal elements other than Li. In this case, the improvement effect of the cycle characteristics becomes more significant compared to the case where the ratio of the transition metal element in the Li layer is not within this range. The ratio of the transition metal element present in the Li layer can be adjusted, for example, by controlling the calcination temperature described later, and generally the higher the calcination temperature, the greater the ratio. The ratio of the transition metal element present in the Li layer is obtained from the Rietveld analysis result of the X-ray diffraction pattern of the lithium transition metal oxide of the present embodiment based on X-ray diffraction measurement.

[0028] The X-ray diffraction pattern was obtained by a powder X-ray diffraction method under the following conditions using a powder X-ray diffractometer (manufactured by Rigaku Corporation, trade name “RINT-TTR”, radiation source Cu—Kα).

[0029] Measuring range: 15-120°

[0030] Scanning speed: 4° / min

[0031] Resolution range: 30-120°

[0032] Background; B-spline

[0033] Contour function; segmentation pseudo-Voigt function

[0034] Constraints: Li(3a)+Ni(3a)=1

[0035] Ni(3a)+Ni(3b)=y

[0036] Y is the ratio of Ni to the total amount of metal elements other than Li in the lithium transition metal oxide (0.90≤y<1.00)

[0037] ICSD No.; 98-009-4814

[0038] In addition, Rietveld analysis of the X-ray diffraction pattern was performed using PDXL2 (Rigaku Corporation), which is Rietveld analysis software.

[0039] The composite oxide (Z) is a secondary particle formed by the aggregation of multiple primary particles. The volume-based median particle size (D50) of the composite oxide (Z) is, for example, 3 μm to 30 μm, preferably 5 μm to 25 μm. The composite oxide (Z) is a secondary particle formed by the aggregation of primary particles, so the D50 of the composite oxide refers to the D50 of the secondary particle. D50 refers to the particle size at which the cumulative frequency from the smaller particle size in the volume-based particle size distribution becomes 50%, also known as the median diameter. The particle size distribution of the composite oxide (Z) can be measured using a laser diffraction particle size distribution measuring device (e.g., MT3000II manufactured by Microtrac BEL Co., Ltd.) using water as the dispersion medium.

[0040] The average particle size of the primary particles constituting the composite oxide (Z) is, for example, 0.05 μm to 1 μm. The average particle size of the primary particles is calculated by averaging the diameters of the circumscribed circles of the primary particles obtained by analyzing a scanning electron microscope (SEM) image of a cross section of secondary particles.

[0041] The composite oxide (Z) contains Ni of 80 mol% or more relative to the total molar number of metal elements other than Li. By setting the content of Ni to 80 mol% or more, a battery with high energy density can be obtained. The content of Ni can be 85 mol% or more relative to the total molar number of metal elements other than Li, or can be 90 mol% or more. The upper limit of the content of Ni is, for example, 95 mol%. It should be noted that the Ni contained in the composite oxide (Z) is, for example, a Ni source for a coating formed on the surface of the negative electrode, and a part of it is dissolved and deposited on the surface of the negative electrode due to charge and discharge, and is included in the coating of the negative electrode 12.

[0042] The composite oxide (Z) contains Co as an essential element as described above. In the composite oxide (Z), the content of Co is less than 7 mol% relative to the total molar number of metal elements other than Li. By adding a small amount of Co to the composite oxide (Z), the cycle characteristics can be effectively improved. It should be noted that even if more than 7 mol% of Co is added, the cycle characteristics do not change, or instead decrease. In addition, the addition of more than 7 mol% of Co leads to undesirable conditions such as reduced capacity and increased cost. Co is effective even in very small amounts, but the lower limit of its content is preferably 2 mol%. The content of Co is preferably 2 to 7 mol% relative to the total molar number of metal elements other than Li, and more preferably 3 to 6 mol%.

[0043] The composite oxide (Z) further contains M1 and M2 as essential components. As described above, M1 is at least one element selected from Ca and Sr, and M2 is at least one element selected from Nb, Zr, Ti, W, Al and Si. By adding a small amount of M1 and M2 to the composite oxide (Z), a stable protective film is formed on both the positive electrode 11 and the negative electrode 12, which is believed to effectively suppress the side reaction of the electrolyte and effectively improve the cycle characteristics. It should be noted that when only either M1 or M2 is added, a sufficient effect cannot be obtained.

[0044] In the composite oxide (Z), the content of M1 is less than 1 mol% relative to the total molar number of metal elements other than Li. Even if more than 1 mol% of M1 is added, the cycle characteristics will not change, or will decrease. In addition, the addition of more than 1 mol% of M1 will cause undesirable conditions such as an increase in resistance and a decrease in charge capacity.

[0045] The content of M1 is preferably lower than the content of Co and M2. In this case, the effect of improving the cycle characteristics becomes more significant. M1 is effective even in a very small amount, but the lower limit of its content is preferably 0.05 mol%. The content of M1 is preferably 0.05 to 1 mol, more preferably 0.1 to 0.5 mol, relative to the total molar number of metal elements other than Li. When Ca and Sr are added as M1, it is preferred that the total of their contents is within this range.

[0046] M1 exists at least at the interface between primary particles inside the secondary particles of the composite oxide (Z). In this case, it is believed that the inhibitory effect of side reactions becomes significant, and the cycle characteristics can be effectively improved. The presence of M1 at the interface of the primary particles can be confirmed by TEM-EDX (transmission microscopy-energy dispersive X-ray spectroscopy). As described in detail later, when the average porosity of the secondary particles is 1 to 5%, it becomes easy to make M1 selectively exist at the interface between the primary particles. M1 exists, for example, in a state of being dispersed without omission at the interface between each primary particle. It should be noted that M1 can also be attached to the surface of the secondary particles.

[0047] In the composite oxide (Z), the content of M2 is less than 3 mol% relative to the total molar number of metal elements other than Li. Even if more than 3 mol% of M2 is added, the cycle characteristics will not change, or will decrease instead. In addition, the addition of more than 3 mol% of M2 will lead to undesirable conditions such as an increase in resistance and a decrease in charging capacity. It should be noted that the M2 contained in the composite oxide (Z) is the M2 source of the film formed on the surface of the negative electrode, a part of which is dissolved and deposited on the surface of the negative electrode due to charging and discharging, and is contained in the film of the negative electrode 12.

[0048] The content of M2 is, for example, lower than the content of Co and higher than the content of M1. In this case, the effect of improving the cycle characteristics becomes more significant. M2 is effective even in a very small amount, but the lower limit of its content is preferably 0.1 mol%. The content of M2 is preferably 0.1 to 3 mol%, more preferably 0.3 to 2 mol%, relative to the total molar number of metal elements other than Li. When adding two or more elements as M2, it is preferred that the total of their contents is within this range.

[0049] The composite oxide (Z) preferably contains at least one element selected from Nb, Zr, Ti and W as M2. Among them, it is more preferred to contain at least Nb or W, and particularly preferably to contain Nb. As an example of a suitable combination of M2, Nb and W, Nb and Ti, Nb and Zr, W and Ti, and W and Zr can be cited. The content of Nb is particularly preferably 0.35 to 1 mol% relative to the total molar number of metal elements other than Li. When the content of Nb is within this range, the improvement effect of the cycle characteristics becomes more significant.

[0050] The existence state of M2 in the composite oxide (Z) is not particularly limited. M2, for example, forms a solid solution with other metal elements such as Ni. In particular, Nb preferably forms a solid solution. Preferably, more than 70% of the Nb contained in the composite oxide (Z) is solid-dissolved in the composite oxide (Z), and it is particularly preferred that substantially all Nb is solid-dissolved. The amount of M2 dissolved can be confirmed by an inductively coupled plasma emission spectrophotometer (ICP-AES) or energy dispersive X-ray spectroscopy (EDS). W can form a solid solution with other metal elements such as Ni like Nb, and can also exist on the surface of primary particles like M1.

[0051] The composite oxide (Z) may contain elements other than Li, Ni, Co, M1, and M2. Examples of the metal element include Mn, Cu, Na, K, and Ba. The composite oxide (Z) preferably contains Mn. When the composite oxide (Z) contains Mn, the content of Mn is preferably 1 to 10 mol% relative to the total molar number of metal elements other than Li. The content of Mn is higher than the content of M1 and M2, and may be equal to the content of Co.

[0052] The content of the elements constituting the composite oxide (Z) can be measured by using an inductively coupled plasma atomic emission spectrophotometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.

[0053] The average porosity of the secondary particles of the composite oxide (Z) is 1 to 5% as described above. When the average porosity is within this range, it becomes easy for M1 to be selectively present at the interface between the primary particles, and it is believed that the inhibitory effect of side reactions becomes higher. In addition, the cycle characteristics are effectively improved. When the average porosity is lower than 1%, M1 easily enters the interior of the primary particles, and the improvement effect of the cycle characteristics cannot be obtained. On the other hand, when the average porosity exceeds 5%, the reaction area with the electrolyte becomes too large, and the cycle characteristics are reduced. It should be noted that not only the average value of the porosity is preferably 1 to 5%, but the median value is also preferably 1 to 5%.

[0054] The porosity of the secondary particles is the ratio of the area of ​​pores to the cross section of the secondary particles, and is calculated by the formula: (area of ​​pores / cross-sectional area of ​​secondary particles) × 100. The porosity can also be calculated from the total area of ​​pores contained in the entire cross section of the secondary particles or per unit area.

[0055] The porosity is obtained by analyzing the SEM image of the cross section of the secondary particles. For the extraction of the primary particles and pores, it is appropriate to select image analysis software such as Image J, Avizo-Materials Science, etc. to perform noise removal on the SEM image, and apply the brightness threshold combined in edge detection and MarkerBased-Watershed method to extract the primary particles and pores. It should be noted that the area detected by Watershed with the high brightness value area as the center is defined as the primary particle, and the low brightness area is defined as the pore.

[0056] The secondary particles of the composite oxide (Z) contain a large number of small pores. Most or all of the pores are formed in the gaps between the primary particles. The average porosity of the secondary particles is more preferably 1.2 to 4.5, and particularly preferably 1.5 to 3.5. The porosity of the secondary particles can be adjusted to the target range, for example, by controlling the calcination conditions described later.

[0057] The composite oxide (Z) can be synthesized, for example, by mixing and calcining a transition metal oxide containing Ni, Co, Mn, etc., an M1 raw material, an M2 raw material, and a Li raw material such as lithium hydroxide (LiOH). Alternatively, the composite oxide (Z) can be synthesized by mixing and calcining a transition metal oxide containing Ni, Co, Mn, etc., an M1 raw material, and an M2 raw material to synthesize a composite oxide containing Ni, Co, Mn, M1, and M2, and then adding a Li raw material and calcining again.

[0058] The calcination process of the composite oxide (Z) includes, for example, the following steps: a first step of obtaining a composite oxide containing Ni, etc., a second step of mixing the composite oxide and a lithium compound to obtain a mixture, and a third step of calcining the mixture. The compound containing M1 and the compound containing M2 are preferably added in the second step. In addition, M2 may also be added in the first step.

[0059] In the first step, for example, a solution containing metal salts of Ni, Mn, etc. is stirred while an alkaline solution such as sodium hydroxide is added dropwise to adjust the pH to the alkaline side (e.g., 8.5 to 12.5), thereby precipitating (coprecipitating) a composite hydroxide containing Ni, Mn, etc. The composite hydroxide is calcined to obtain a composite oxide containing Ni, Mn, etc. The calcination temperature is not particularly limited, and as an example, is 250°C to 600°C.

[0060] In the second step, for example, the composite oxide obtained in the first step, the lithium compound, the compound containing M1, and the compound containing M2 are mixed. Examples of lithium compounds include Li2CO3, LiOH, Li2O2, Li2O, LiNO3, LiNO2, Li2SO4, LiOH·H2O, LiH, and LiF. The composite oxide and the lithium compound are preferably mixed in a molar ratio of the total amount of metal elements other than Li to Li of 1:0.98 to 1:1.12.

[0061] The calcining process of the mixture in the third process is, for example, a multi-stage calcining process, which includes at least the following processes: a first calcining process of calcining at 450°C to 680°C under an oxygen gas flow; and a second calcining process of calcining the calcined product obtained by the first calcining process at a temperature exceeding 680°C under an oxygen gas flow. In the first calcining process, the temperature is increased to a first set temperature of less than 680°C at a first heating rate of 0.2°C / min to 4.5°C / min. In the second calcining process, the temperature is increased to a second set temperature of less than 900°C at a temperature of 1°C / min to 3.5°C / min. In the second calcining process, if the heating rate is lower than 1°C, the crystal growth of the primary particles progresses, and the pores inside the secondary particles decrease, so that the composite oxide (Z) whose average porosity meets the specified value cannot be obtained. It should be noted that the first and second heating rates can be set multiple according to the specified temperature range within the above range.

[0062] The holding time of the first set temperature in the first sintering step is preferably less than 5 hours, more preferably less than 3 hours. The holding time of the first set temperature refers to the time for maintaining the first set temperature after reaching the first set temperature, and the holding time may also be zero. The holding time of the second set temperature in the second sintering step is preferably 1 hour to 10 hours, more preferably 1 hour to 5 hours. The holding time of the second set temperature refers to the time for maintaining the third set temperature after reaching the second set temperature. Even when the second set time is set to be greater than 10 hours, the crystal growth of the primary particles progresses, and the pores inside the secondary particles decrease, so that the composite oxide (Z) whose average porosity meets the specified value cannot be obtained. The sintering of the mixture is carried out, for example, in an oxygen gas flow with an oxygen concentration of more than 60%, and the flow rate of the oxygen gas flow is set to 100% per 10 cm3 The firing furnace is 0.2 mL / min to 4 mL / min and 0.3 L / min or more per 1 kg of the mixture.

[0063] As an example of the above-mentioned M1 raw material, Ca(OH)2, CaHPO4, Ca(H2PO4)2, Ca3(PO4)2, CaO, CaCO3, CaSO4, Ca(NO3)2, CaCl2, CaAlO4, Sr(OH)2, Sr(OH)2·8H2O, SrO, SrCO3, SrSO4, Sr(NO3)2, etc. can be listed, but in order to reduce the amount of water generated during firing, they can also be used after drying and dehydration. In addition, these compounds can also be pulverized to a particle size of 0.1 to 20 μm. As an example of the above-mentioned M2 raw material, when M2 is Nb, Nb2O5, Nb2O5·nH2O, WO3, Li2WO4, TiO2, Ti(OH)4, ZrO2, Al(OH)3, Al2O3, Al(NO3)3, MoO3, Li2MoO4, SiO, SiO2, B2O3, LiBO3, Li2B4O7, P2O5, MgO, Mg(OH)2, Fe2O3, etc. can be listed.

[0064] The burned product obtained in the third step is washed with water to remove impurities, and the washed burned product is heated and dried. As needed, the burned product is crushed, classified, etc., and the D50 of the positive electrode active material is adjusted to the target range. The washed burned product can also be dried at a temperature lower than 100°C. An example of a suitable drying temperature is 250°C to 600°C. The drying process can be carried out under vacuum or in the atmosphere. An example of the drying process time is 1 hour to 5 hours.

[0065] [negative electrode]

[0066] The negative electrode 12 has a negative electrode core and a negative electrode composite material layer disposed on the surface of the negative electrode core. The negative electrode core can use a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, a thin film of the metal disposed on the surface, and the like. The negative electrode composite material layer preferably includes a negative electrode active material and a binding material, and is disposed on both sides of the negative electrode core except for the portion to which the negative electrode lead 21 is connected. The negative electrode 12 can be manufactured, for example, by coating a negative electrode composite material slurry containing a negative electrode active material and a binding material on the surface of the negative electrode core, drying the coating, and then compressing it to form a negative electrode composite material layer on both sides of the negative electrode core, thereby enabling the negative electrode 12 to be manufactured.

[0067] The negative electrode composite material layer generally contains a carbon material that reversibly absorbs and releases lithium ions as a negative electrode active material. A suitable example of a carbon material is graphite such as natural graphite such as flaky graphite, blocky graphite, and earthy graphite, blocky artificial graphite (MAG), and artificial graphite such as graphitized mesophase carbon microbeads (MCMB). In addition, as a negative electrode active material, an active material containing at least one of an element alloyed with Li such as Si, Sn, and a material containing the element can also be used. A suitable example of the active material is a SiO2 phase or a silicate phase such as a lithium silicate, or a Si-containing material in which Si particles are dispersed in an amorphous carbon phase. Graphite and a Si-containing material can also be used in combination as a negative electrode active material.

[0068] The binder contained in the negative electrode composite material layer may be fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., as in the case of the positive electrode 11, preferably styrene-butadiene rubber (SBR). In addition, the negative electrode composite material layer preferably further comprises CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc. Among them, it is suitable to use SBR in combination with CMC or its salt, PAA or its salt.

[0069] The negative electrode 12 has a coating containing M2 formed on the surface of the negative electrode composite material layer (hereinafter sometimes referred to as "negative electrode coating"). It is believed that the negative electrode coating is formed by depositing M2 in the composite oxide (Z) dissolved by charging and discharging on the surface of the negative electrode composite material layer. That is, the negative electrode coating contains M2 derived from the composite oxide (Z). The negative electrode coating is formed, for example, by charging and discharging less than 10 cycles. When a negative electrode coating containing a specified amount of M2 is formed, an improvement in the cycle characteristics can be obtained. The presence of the negative electrode coating can be confirmed by X-ray photoelectron spectroscopy (XPS).

[0070] The content of M2 in the negative electrode 12 is 1000 to 10000 ppm relative to the total mass of the negative electrode composite material layer and the negative electrode coating. Here, the content of M2 refers to the content when charging and discharging are performed under the same conditions as the cycle test described later. When the content of M2 is less than 1000 ppm or exceeds 10000 ppm, the improvement effect of the cycle characteristics cannot be obtained.

[0071] The content of M2 in the negative electrode 12 varies depending on the composition of the composite oxide (Z), in particular, the content of M2 in the composite oxide (Z). In other words, the content of M2 in the composite oxide (Z) is adjusted so that the content of M2 in the negative electrode 12 is 1000 to 10000 ppm. In addition, the content of M2 in the negative electrode 12 also varies depending on the charge and discharge conditions. For example, when the charge termination voltage is increased and the discharge depth is deepened, there is a tendency for the content of M2 to increase.

[0072] The content of M2 with respect to the total mass of the negative electrode mixture layer and the negative electrode coating can be calculated by the following method. The content of M1 and Ni described below can also be calculated by the same method.

[0073] (1) Ion exchange water was added to the negative electrode 12 to separate the negative electrode composite material layer and the coating from the negative electrode core, and the weights of the negative electrode composite material layer and the coating were measured.

[0074] (2) Add aqua regia and hydrofluoric acid to the separated negative electrode composite material layer and coating, heat and dissolve them, filter out insoluble substances such as carbon, and prepare an aqueous solution. The aqueous solution is fixed to volume with ion exchange water, and the M2 concentration is measured by ICP-AES, and the result is set as the M2 content in the negative electrode.

[0075] (3) The content of M2 in the negative electrode 12 measured in (2) is divided by the weight of the negative electrode mixture layer and the coating measured in (1) to obtain the content of M2 in the negative electrode 12 .

[0076] The negative electrode coating may also contain Ni and M1. Ni, M1 and M2 contained in the negative electrode coating are Ni and M1 derived from the composite oxide (Z) in the same manner. It is believed that Ni, M1 and M2 in the composite oxide (Z) dissolved by charging and discharging are deposited together on the surface of the negative electrode composite material layer to form the negative electrode coating.

[0077] In the negative electrode 12, the ratio of the content of M2 to the content of Ni (M2 / Ni), that is, the mass ratio of M2 to Ni is preferably 0.3 to 2, and more preferably 0.3 to 0.8. If M2 / Ni is within this range, the effect of improving the cycle characteristics becomes more significant. Here, M2 / Ni refers to the ratio when charging and discharging under the same conditions as the cycle test described later.

[0078] M2 / Ni varies according to the composition of the composite oxide (Z), in particular, the molar ratio of M2 to Ni. In other words, it is preferred to adjust the molar ratio of M2 to Ni in the composite oxide (Z) so that M2 / Ni in the negative electrode 12 is within the above range. It should be noted that M2 / Ni in the negative electrode 12 may also vary slightly depending on the charge and discharge conditions.

[0079] [Separator]

[0080] The separator 13 uses a porous sheet with ion permeability and insulation. As specific examples of the porous sheet, microporous films, woven fabrics, nonwoven fabrics, etc. can be cited. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, etc. are suitable. The separator 13 can be a single-layer structure or a multi-layer structure. In addition, a resin layer with high heat resistance such as aramid resin can be formed on the surface of the separator 13.

[0081] A filler layer containing an inorganic filler may also be formed at the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. Examples of the inorganic filler include oxides containing metal elements such as Ti, Al, Si, and Mg, and phosphate compounds. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode 11, the negative electrode 12, or the separator 13.

[0082] Example

[0083] Hereinafter, the present disclosure will be further described based on examples, but the present disclosure is not limited to these examples.

[0084] <Example 1>

[0085] [Synthesis of lithium transition metal composite oxide (positive electrode active material)]

[0086] After mixing a composite oxide containing a general formula of Ni, Co, and Mn, calcium hydroxide, strontium hydroxide, niobium hydroxide, and titanium oxide at a predetermined ratio, lithium hydroxide is mixed so that the molar ratio of the metal elements in the mixture to Li is 1:1.03. The predetermined ratio is set as follows: the content of Ca is 0.3 mol%, the content of Sr is 0.1 mol%, the content of Nb is 0.5 mol%, and the content of Ti is 1.5 mol%, relative to the total molar number of the metal elements other than Li.

[0087] The mixture was placed in a sintering furnace and heated under an oxygen flow with an oxygen concentration of 95% (per 10 cm 3 The mixture was calcined at a rate of 2 mL / min and a flow rate of 5 L / min per 1 kg of the mixture) from room temperature to 650°C at a heating rate of 1.0°C / min. Then, the mixture was calcined at a rate of 1.5°C / min from 650°C to 740°C and maintained for 2 hours, and the calcined product was washed with water to obtain a lithium transition metal composite oxide.

[0088] The lithium transition metal composite oxide was analyzed by ICP-AES. The composition of the composite oxide was Li 0.98 Ni 0.886 Co 0.05 Mn 0.05 Ca 0.003 Sr 0.001 Nb 0.005 Ti 0.005 O2. In addition, by performing Rietveld analysis on an X-ray diffraction pattern obtained by powder X-ray diffraction measurement under predetermined conditions, it was confirmed that the ratio of the transition metal element present in the Li layer was 4.7 mol % relative to the total molar number of metal elements other than Li.

[0089] The average porosity of the secondary particles was determined from the cross-sectional SEM image of the lithium transition metal composite oxide (secondary particles) using the above analytical method. The average porosity was 2.5%. In addition, the presence of Ca and Sr at the interface between the primary particles inside the secondary particles was confirmed by TEM-EDX (transmission microscope-energy dispersive X-ray spectroscopy).

[0090] [Production of positive electrode]

[0091] The above-mentioned positive electrode active material, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 98:1:1, and N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium to prepare a positive electrode composite material slurry. Next, the positive electrode composite material slurry is applied on the positive electrode core formed by aluminum foil, the coating film is dried, and after compression, the positive electrode core is cut into a specified electrode size to obtain a positive electrode having a positive electrode composite material layer formed on both sides of the positive electrode core. It should be noted that an exposed portion exposed on the surface of the positive electrode core is provided on a part of the positive electrode. The amount of positive electrode active material in the positive electrode composite material layer is 0.49g.

[0092] [Production of negative electrode]

[0093] Natural graphite is used as the negative electrode active material. The negative electrode active material, sodium carboxymethyl cellulose (CMC-Na) and a dispersant of styrene-butadiene rubber (SBR) are mixed at a solid content mass ratio of 100:1:1, and water is used as a dispersion medium to prepare a negative electrode composite material slurry. The negative electrode composite material slurry is applied to both sides of a negative electrode core formed of copper foil, and after the coating film is dried, the coating film is rolled using a roller and cut into a specified electrode size to obtain a negative electrode having a negative electrode composite material layer formed on both sides of the negative electrode core. It should be noted that an exposed portion where the surface of the negative electrode core is exposed is provided on a part of the negative electrode.

[0094] [Preparation of non-aqueous electrolyte]

[0095] A non-aqueous electrolyte was prepared by dissolving LiPF6 at a concentration of 1.2 mol / L in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (MEC) and dimethyl carbonate (DMC) in a volume ratio of 3:3:4 (25°C).

[0096] [Fabrication of test battery cell (non-aqueous electrolyte secondary battery)]

[0097] An aluminum lead was installed on the exposed portion of the positive electrode, and a nickel lead was installed on the exposed portion of the negative electrode. The positive electrode and the negative electrode were spirally wound with a polyolefin separator interposed therebetween, and then press-formed in the radial direction to produce a flat wound electrode body. The electrode body was housed in an outer case shell composed of an aluminum laminate sheet, and after the non-aqueous electrolyte was injected, the opening of the outer case was sealed to obtain a test battery cell A1.

[0098] For the above-mentioned test battery cells, the capacity retention rate after the cycle test was evaluated using the following method. In addition, XPS confirmed that a negative electrode coating was formed on the surface of the negative electrode composite material layer after the cycle test. The content of M2 (Nb, Ti in Example 1) and M2 / Ni in the negative electrode were calculated by the above-mentioned method using ICP-AES. In Table 1, Examples 1 to 6 are referred to as A1 to A6, and Comparative Examples 1 to 5 are referred to as B1 to B5. The capacity retention rate of each test battery cell shown in Table 1 is a relative value when the capacity retention rate of the test battery cell of Comparative Example 1 (B1) is set to 100.

[0099] [Evaluation of capacity maintenance rate after cycle test]

[0100] For the above test battery cell, at a temperature of 45°C, constant current charging was performed at a constant current of 0.5It until the battery voltage reached 4.3V, and constant voltage charging was performed at 4.3V until the current value reached 1 / 50It. Then, constant current discharge was performed at a constant current of 0.5It until the battery voltage reached 2.5V. This charge and discharge cycle was repeated 100 times. The discharge capacity of the first cycle and the discharge capacity of the 100th cycle of the cycle test were obtained, and the capacity retention rate was calculated according to the following formula.

[0101] Capacity retention rate (%) = (100th cycle discharge capacity ÷ 1st cycle discharge capacity) × 100

[0102] <Example 2>

[0103] Calcium hydroxide was used as the M1 raw material, niobium hydroxide and tungsten oxide were used as the M2 raw materials, and the mixing ratio of each raw material was changed to obtain the element ratio shown in Table 1 to synthesize a lithium transition metal composite oxide. Otherwise, a test battery cell was prepared in the same manner as in Example 1 to evaluate the performance.

[0104] <Example 3>

[0105] Calcium hydroxide was used as the M1 raw material, tungsten oxide and zirconium oxide were used as the M2 raw materials, and the mixing ratio of each raw material was changed to obtain the element ratio shown in Table 1 to synthesize a lithium transition metal composite oxide. Otherwise, a test battery cell was prepared in the same manner as in Example 1 to evaluate the performance.

[0106] <Example 4>

[0107] Calcium hydroxide was used as the M1 raw material, tungsten oxide and titanium oxide were used as the M2 raw materials, and the mixing ratio of each raw material was changed to obtain the element ratio shown in Table 1 to synthesize a lithium transition metal composite oxide. Otherwise, a test battery cell was prepared in the same manner as in Example 1 to evaluate the performance.

[0108] <Example 5>

[0109] Calcium hydroxide was used as the M1 raw material, tungsten oxide was used as the M2 raw material, and the mixing ratio of each raw material was changed to obtain the element ratio shown in Table 1 to synthesize a lithium transition metal composite oxide. Otherwise, a test battery cell was prepared in the same manner as in Example 1 and performance was evaluated.

[0110] <Example 6>

[0111] A lithium transition metal composite oxide was synthesized by using calcium hydroxide as the M1 raw material and niobium oxide as the M2 raw material, respectively, by changing the mixing ratio of each raw material to obtain the element ratio shown in Table 1. A test battery cell was prepared in the same manner as in Example 1, and performance was evaluated.

[0112] <Comparative Example 1>

[0113] A test cell was produced in the same manner as in Example 1 except that the M1 raw material and the M2 raw material were not used in the synthesis of the lithium transition metal composite oxide, and performance evaluation was performed.

[0114] <Comparative Example 2>

[0115] A test battery cell was prepared in the same manner as in Example 1, except that calcium hydroxide was used as the M1 raw material instead of the M2 raw material, and the mixing ratio of each raw material was changed to obtain the element ratio shown in Table 1 to synthesize a lithium transition metal composite oxide, and performance evaluation was performed.

[0116] <Comparative Example 3>

[0117] A test cell was prepared in the same manner as in Example 1 except that niobium hydroxide was used as the M2 raw material instead of M1 and the mixing ratio of each raw material was changed to obtain the element ratio shown in Table 1 to synthesize a lithium transition metal composite oxide, and performance evaluation was performed.

[0118] <Comparative Example 4>

[0119] Instead of using M2 raw material, calcium hydroxide was used as M1 raw material. The heating rate in the second sintering step was changed to 0.5°C / m, and the holding time of the second set temperature was changed to 16 hours to synthesize a lithium transition metal composite oxide. Otherwise, a test battery cell was prepared in the same manner as in Example 1, and the performance was evaluated.

[0120] <Comparative Example 5>

[0121] A test cell was prepared in the same manner as in Example 6 except that the temperature increase rate in the second calcination step was changed to 0.5° C. / m and the holding time at the second set temperature was changed to 16 hours to synthesize a lithium transition metal composite oxide, and performance evaluation was performed.

[0122] [Table 1]

[0123]

[0124] As shown in Table 1, the test battery cells of the embodiments have higher capacity retention rates after the cycle test and better cycle characteristics than the test battery cells of the comparative examples. By comparing the results of the test battery cells of Examples 1-6 with those of Comparative Examples 1-3, it can be seen that by containing both M1 and M2, the capacity retention rate is specifically improved compared to the case where the positive electrode active material contains either M1 or M2. In addition, by comparing the results of Example 6 with Comparative Examples 4 and 5, it can be seen that by making the average porosity greater than 1 and containing both M1 and M2, the capacity retention rate is specifically improved compared to the case where the average porosity is less than 1. That is, by making the average porosity greater than 1 and containing a positive electrode active material having a specified amount of M1 and M2, and a negative electrode coating containing a specified amount of M2 derived from the positive electrode active material, the charge and discharge cycle characteristics of the battery are greatly improved.

[0125] The present disclosure is further described through the following embodiments.

[0126] Composition 1:

[0127] A non-aqueous electrolyte secondary battery comprises a positive electrode, a negative electrode and a non-aqueous electrolyte.

[0128] The positive electrode comprises a lithium transition metal composite oxide containing Ni, Co, M1 (M1 is at least one element selected from Ca and Sr), and M2 (M2 is at least one element selected from Nb, Zr, Ti, W, Al, Mo, Fe, B, P, Mg and Si),

[0129] In the aforementioned lithium transition metal composite oxide,

[0130] The content of Ni is 80 mol% or more relative to the total molar number of metal elements excluding Li.

[0131] The content of Co is 7 mol% or less relative to the total molar number of metal elements excluding Li.

[0132] The content of M1 is 1 mol% or less relative to the total molar number of metal elements excluding Li.

[0133] The content of M2 is 3 mol% or less relative to the total molar number of metal elements excluding Li.

[0134] The lithium transition metal composite oxide is a secondary particle formed by agglomeration of a plurality of primary particles, the average porosity of the secondary particle is 1 to 5%, and M1 exists at least at the interface between the primary particles inside the secondary particle.

[0135] The negative electrode comprises a negative electrode composite material layer containing a negative electrode active material and a coating containing M2 formed on the surface of the negative electrode composite material layer. The content of M2 in the negative electrode is 1000 to 10000 ppm relative to the total mass of the negative electrode composite material layer and the coating.

[0136] Composition 2:

[0137] The nonaqueous electrolyte secondary battery according to Configuration 1, wherein the lithium-transition metal composite oxide contains Mn.

[0138] Composition 3:

[0139] The nonaqueous electrolyte secondary battery according to configuration 1 or 2, wherein in the lithium transition metal composite oxide, the ratio of the transition metal element present in the Li layer is 3 to 7 mol % relative to the total molar number of metal elements other than Li.

[0140] Composition 4:

[0141] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein the lithium transition metal composite oxide contains Nb as M2,

[0142] In the lithium transition metal composite oxide, the content of Nb is 0.35 to 1 mol % based on the total number of moles of metal elements excluding Li.

[0143] Composition 5:

[0144] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 4, wherein the content of Co in the lithium transition metal composite oxide is 2 to 7 mol % relative to the total number of moles of metal elements excluding Li.

[0145] Description of Reference Numerals

[0146] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket.

Claims

1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The positive electrode comprises a lithium transition metal composite oxide containing Ni, Co, M1, and M2, wherein: M1 is at least one element selected from Ca and Sr, M2 is at least one element selected from Nb, Zr, Ti, W, Al, Mo, Fe, B, P, Mg and Si, In the lithium transition metal composite oxide, The content of Ni is 80 mol% or more relative to the total molar number of metal elements excluding Li. The content of Co is 7 mol% or less relative to the total molar number of metal elements excluding Li. The content of M1 is 1 mol% or less relative to the total molar number of metal elements excluding Li. The content of M2 is 3 mol% or less relative to the total molar number of metal elements excluding Li. The lithium transition metal composite oxide is a secondary particle formed by agglomeration of a plurality of primary particles, the average porosity of the secondary particle is 1 to 5%, and M1 exists at least at the interface between the primary particles inside the secondary particle. The negative electrode comprises a negative electrode composite material layer including a negative electrode active material and a coating film containing M2 formed on the surface of the negative electrode composite material layer. The content of M2 in the negative electrode is 1000 to 10000 ppm relative to the total mass of the negative electrode composite material layer and the coating film.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The lithium transition metal composite oxide contains Mn.

3. The nonaqueous electrolyte secondary battery according to claim 1, wherein In the lithium transition metal composite oxide, the ratio of the transition metal element present in the Li layer is 3 to 7 mol % relative to the total molar number of metal elements other than Li.

4. The nonaqueous electrolyte secondary battery according to claim 1, wherein The lithium transition metal composite oxide contains Nb as M2, In the lithium transition metal composite oxide, the content of Nb is 0.35 to 1 mol % relative to the total molar number of metal elements excluding Li.

5. The nonaqueous electrolyte secondary battery according to claim 1, wherein In the lithium transition metal composite oxide, the content of Co is 2 to 7 mol % relative to the total molar number of metal elements excluding Li.

Citation Information

Patent Citations

  • Nonaqueous electrolyte secondary battery

    JP2006310181A

  • Lithium transition metal system compound powder, method of manufacturing the same, and spray-dried material to become its calcination precursor, and positive electrode for lithium secondary battery using the same, and lithium secondary cell

    JP2009289726A